2020
DOI: 10.3390/antiox9030243
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Diet Supplementation with Pomegranate and Bitter Melon on Lipidomic Profile of Serum and Cancerous Tissues of Rats with Mammary Tumours

Abstract: The aim of this study was to present overall lipid profile of organisms with ongoing neoplastic process and applied diet supplementation with pomegranate seed oil (PSO) and bitter melon extract (BME). The following were quantified in serum and cancerous tissues of rats suffering from mammary tumours: fatty acids, conjugated fatty acids and sterols, their oxidised metabolites (malondialdehyde and oxysterols) and lipoxygenase (LOX) metabolites of polyunsaturated fatty acids. The obtained results indicate that ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 56 publications
0
8
0
1
Order By: Relevance
“…It was previously established that the cancerous process is characterized by changed metabolism, including increased utilization of lipid compounds, e.g., by uptake from an extracellular matrix or de novo synthesis [ 13 , 14 , 15 ]. We previously revealed the significant differences in lipidomic profile in serum and tissues (mammary, cardiac, hepatic) generated by developing breast cancer [ 7 , 8 , 9 , 16 ]. We hypothesized that modified lipid metabolism in cancerous process may result inter alia from alteration in the activity of enzymes involved in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously established that the cancerous process is characterized by changed metabolism, including increased utilization of lipid compounds, e.g., by uptake from an extracellular matrix or de novo synthesis [ 13 , 14 , 15 ]. We previously revealed the significant differences in lipidomic profile in serum and tissues (mammary, cardiac, hepatic) generated by developing breast cancer [ 7 , 8 , 9 , 16 ]. We hypothesized that modified lipid metabolism in cancerous process may result inter alia from alteration in the activity of enzymes involved in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously observed that pomegranate seed oil (PSO) and bitter melon fruit extract (BME) can change the cellular membrane lipid profile of different tissues (hepatic, cardiac, mammary) and that this impact depends on the physiological condition or developing pathological condition [ 7 , 8 , 9 ]. Based on those results we assumed that similar influence can be exerted on an ER lipid profile, which in turn can change the activity of microsomal enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…The oxysterol 27OHC is the product of cholesterol oxidation by the ubiquitous and constitutive mitochondrial hydroxylase CYP27A1 [20] and represents the most abundant oxysterol in human plasma [21]. The role of this oxysterol in cancer is highly debated and related literature is quite controversial, given that different experimental approaches and conditions were employed, a wide variety of cancer types was assessed [22], and the oxysterol content varied significantly in the single tumors [23]. As far as human adrenal cancer cells are concerned, this paper provides solid evidence of specific cytotoxic and pro-apoptotic actions of 27OHC, which matches the in vitro effect exerted by an identical micromolar amount of mitotane ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Además, diferentes partes de P. granatum se han utilizado en la medicina tradicional, ya que esta planta posee diversos efectos terapéuticos como antioxidante, antiinflamatorio, antimicrobiano o anticancerígeno contra múltiples enfermedades y dolencias; por ejemplo, en la prevención y tratamiento de fiebre, úlceras, diarreas, hemorragias, infecciones microbianas, diabetes, anemia, osteoartritis o trastornos respiratorios (Larrosa et al, 2010). Gracias a ello, el estudio del potencial farmacológico de los componentes químicos y sustancias bioactivas y antioxidantes de esta planta ha resultado de profundo interés para la comunidad científica, sobre todo en la última década (Garcia-Niño y Zazueta, 2015; Bialek et al, 2020).…”
Section: La Granada (Punica Granatum L)unclassified